Pengaruh Store Atmosphere dan Harga terhadap Keputusan Pembelian di Golden Leaf Restaurant Kelapa Gading - Wardanah, Iga Dwi; Budiarto, Samuel Felix; Dewantara, Yudhiet Fajar (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The increase in consumption of Chinese dishes in recent years has occurred worldwide and has also occurred in Indonesia. With the increasing interest in buying and consuming Chinese dishes, it also affects the growth of restaurants, especially Chinese restaurants, with the existence of intense competition with the atmosphere of each shop having its own uniqueness or characteristics. This study aims to find out whether Store Atmosphere and Prices have an influence on Consumer Purchase Decisions. This research was conducted at a Chinese restaurant in Kelapa Gading, North Jakarta, namely Golden Leaf Restaurant. This research was conducted for the reason that there was an increase in sales due to the available Store Atmosphere and the prices provided for restaurant dishes, namely Chinese dishes at the Golden Leaf Kelapa Gading Restaurant. This research uses quantitative research, the analytical method used is descriptive statistics, the research instrument test consists of a validity test and a reliability test. Then there are the classic assumptions consisting of normality tests, multicollinearity tests, and heteroscedasticity tests. Finally, there is a hypothesis test consisting of a T test, F test, test of the coefficient of determination, and multiple linear regression tests. The sample used in this study was 97 people with the respondent's criteria, namely having made transactions and visits at the Golden Leaf Kelapa Gading Restaurant, North Jakarta. The results of this study are that all the independent variables tested have a positive and significant effect on the dependent variable. The suggestions from this research are to maintain, maintain, and improve the design of the Store Atmosphere for the future as well as adjust the price range which can be said to be superior because it has affordable dish prices, and suggestions for further research can conduct research with different variables such as location, product diversity, product quality, and so on. Keywords: store atmosphere, prices, and purchase decisions